THE STUDY HOW TO ASSEMBLING SMD DEVICE INTEGRATED - Wibowo, Kunto (Universitas Gunadarma, 2008)
Nowadays, the size of electronic components is not macro anymore, but already in micro size, even nano. In designing electronic device using surface mount device (SMD), a number of special components which has better characteristics is oftentimes required because of the demand which can not be tolerated. Hermetic SMD (airproof SMD) is a preference to fulfill the demand for design of small size, light weight, perfect thermal performance, free of switching waves, and also higher circuit efficiency.Keyword(s): assembling, SMD, thermal performance, effcient.Subject Description : B.7.Integrated Circuit | B.7.1. Types and Design Styles | Advanced Technologies